Optimal dose of salbutamol respiratory solution: comparison of three doses with plasma levels. Issue 8 (August 1981) - Walters, E H; Cockroft, A; Griffiths, T; Rocchiccioli, K; Davies, B H
Abstract : Salbutamol solution is usually administered by nebuliser in a dose of 5 mg. Little evidence exists that this is the optimal dose for bronchodilatation or that this dose is without side-effects. Twelve patients with asthma were given increasing doses of salbutamol 1.5 mg, 3.0 mg, 7.5 mg, and placebo. Treatments were administered twice daily for four days in a double-blind manner. Measurements of ventilatory capacity, pulse rate, and tremor were recorded before and for three hours after treatment. There was a significant dose-related response for FEVI and peak flow rate. There was also a significant dose-related response in pulse rate and tremor. The incidence of palpitations was similarly related to dose. Plasma levels of salbutamol were measured before and after treatment with salbutamol and showed a dose related increase in salbutamol absorption which begins to be evident after the 3.0 mg dose. Three milligrams of salbutamol nebuliser solution may be an optimal dose, producing satisfactory bronchodilatation but fewer side-effects related to systemic absorption.